Ethnic conflict and international security - Brown, Michael E. (Michael Edward), 1954- (Princeton University Press, 1993)
During the Cold War, most international relations theorists and strategic studies analysts paid little attention to ethnic and other forms of communal conflict. Disregard for the importance of ethnic and nationality issues in world affairs, always misguided so far as the developing world was concerned, has been overtaken, in stunning fashion, by recent events from Abkhazia to Zaire. The essays in this volume advance our understanding of the causes of ethnic and communal conflict, the regional and international implications of such conflicts, and what the international community can do to minimize the potential for instability and violence. Drawn from recent issues of Survival, they are organized along thematic rather than regional lines, and will be required reading for scholars, students, and policymakers alike. The contributors to the volume include Michael Brown on the causes and implications of ethnic conflict, Anthony Smith on the ethnic sources of nationalism, David Welsh on domestic politics and ethnic conflict, Rene;e de Nevers on democratization and ethnic conflict, and Pierre Hassner on nationalism and internationalism. Jack Snyder writes on nationalism and the crisis of the post-Soviet state, Barry Posen on the security dilemma and ethnic conflict, Kathleen Newland on ethnic conflict and refugees, Jenonne Walker on international mediation of ethnic conflicts, and Robert Cooper and Mats Berdal on outside intervention in ethnic conflicts, Adam Roberts discusses the U.N. and international security, and John Chipman explores managing the politics of parochialism.--Publisher description.